2020
DOI: 10.1126/sciadv.aaz5180
|View full text |Cite
|
Sign up to set email alerts
|

Remote heteroepitaxy of GaN microrod heterostructures for deformable light-emitting diodes and wafer recycle

Abstract: There have been rapidly increasing demands for flexible lighting apparatus, and micrometer-scale light-emitting diodes (LEDs) are regarded as one of the promising lighting sources for deformable device applications. Herein, we demonstrate a method of creating a deformable LED, based on remote heteroepitaxy of GaN microrod (MR) p-n junction arrays on c-Al2O3 wafer across graphene. The use of graphene allows the transfer of MR LED arrays onto a copper plate, and spatially separate MR arrays offer ideal device ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 54 publications
2
70
0
Order By: Relevance
“…Nevertheless, great attention has been paid to remote epitaxy since it has been believed to provide the great benefit of easy separation of the film, which is crystallographically aligned with a substrate. [1][2][3] Several other studies have also demonstrated the facile detachment of a film taken as evidence of remote epitaxy. [4][5][6][7][8] Strictly speaking, however, the easy detachability may not necessarily originate from the 'remoteness' of the remote epitaxy, but simply indicates that the binding between the film and space layer/substrate is weaker than the adhesion of the film to a detacher such as a thermal release tape.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Nevertheless, great attention has been paid to remote epitaxy since it has been believed to provide the great benefit of easy separation of the film, which is crystallographically aligned with a substrate. [1][2][3] Several other studies have also demonstrated the facile detachment of a film taken as evidence of remote epitaxy. [4][5][6][7][8] Strictly speaking, however, the easy detachability may not necessarily originate from the 'remoteness' of the remote epitaxy, but simply indicates that the binding between the film and space layer/substrate is weaker than the adhesion of the film to a detacher such as a thermal release tape.…”
Section: Introductionmentioning
confidence: 95%
“…2 Once the thickness of an inserted 2D material becomes above a critical value, the grown film is no longer crystallographically aligned with the underlying substrate. 2,3 The remote epitaxy strictly requires not only the defect-free growth of 2D material but also the state-of-the-art transfer with precise layer-number control. Nevertheless, great attention has been paid to remote epitaxy since it has been believed to provide the great benefit of easy separation of the film, which is crystallographically aligned with a substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, remote epitaxy using two-dimensional layers such as graphene has received substantial attention. For example, Jeong et al [57] reported the fabrication of deformable microrod LEDs and achieved substrate reuse. Zhao et al [4] and Min et al [58] further reported advances in nanowire and nanorod growth on unconventional substrates such as metal and quartz substrates.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…, Al 2 O 3 ) and that the substrate can be reused for the remote heteroepitaxy of a GaN microrod light emitting diode (LED). 18 Meanwhile, regarding the RE structure of III-nitride/graphene/III-nitride, the stability of the 2-D material on the decomposed III-nitride substrate warrants investigation because the growth temperature of III-nitride is higher than its decomposition temperature, 28 as shown in Fig. S1a, † which means that there is a possibility that column III atoms and N atoms generated from the decomposition of the III-nitride substrate affect graphene.…”
Section: Introductionmentioning
confidence: 99%